Varying screen size for passive video distraction during induction of anesthesia in low‐risk children: A pilot randomized controlled trial. Issue 6 (14th April 2019) - Rodriguez, Samuel T.; Jang, Olivia; Hernandez, Jessica Maya; George, Alexandria Joseph; Caruso, Thomas J.; Simons, Laura E.
Summary: Background: Preoperative anxiety affects up to 65% of children who undergo anesthesia induction and often results in uncooperative behavior. Electronic devices have been used to distract children to reduce anxiety and create a more enjoyable preoperative experience. Few studies have compared the effects of different video delivery systems on preoperative anxiety. Aims: The primary aim was to determine if a large projection‐based video screen mounted to a patient's bed decreased anxiety when compared to a tablet during mask induction of anesthesia in children from 4‐10 years of age. Methods: We performed a prospective, randomized trial to determine differences in our primary outcome, preoperative anxiety, between the large Bedside Entertainment and Relaxation Theater (BERT) and a smaller tablet screen. Secondary outcomes included (a) induction compliance; (b) child fear; (c) frequency of emergence delirium; and (d) satisfaction. Results: In examining the primary outcome for 52 patients, there was a main effect for time on mYPAS scores, f (2, 51) = 13.18, P < 0.01. mYPAS scores significantly increased across time for both groups. The interaction for time (T0, T1 or T2) × group (BERT vs Tablet) was not significant, f (2, 51) = 1.96, P = 0.15; thus changes in mYPAS scores across time did not differ by group status. There was no significant difference in induction compliance, child fear, emergence delirium, or satisfaction between the two groups. Conclusion: In a low‐risk population, preoperative anxiety was low and induction compliance was high when pairing screen‐based distraction interventions, regardless of size, with parental presence at induction of anesthesia.